2002
DOI: 10.1289/ehp.02110s2323
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorated housing contributes to high cockroach allergen levels in inner-city households.

Abstract: The high prevalence of childhood asthma in low-income, inner-city populations is not fully understood but has been at least partly attributed to the disproportionate exposures associated with socioeconomic disadvantage. The contribution of indoor allergens to asthma is well documented, but links between socioeconomic disadvantage and indoor allergen levels are not clear. We investigated levels of cockroach allergens (Bla g 2) in a sample of 132 Dominican or African American low-income households with young chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 31 publications
6
122
1
1
Order By: Relevance
“…We also did not find significant associations between endotoxin concentration or load and any of the questions addressing mold or housing disrepair (Table I), or when analyzing using a previously described housing disrepair scale as an independent variable in linear regression (β=0.02, p=0.75 for concentration endotoxin; β=0.014, p=0.82 for load) (23 …”
Section: Associations Between Cleaning Habits Built Environment and mentioning
confidence: 60%
“…We also did not find significant associations between endotoxin concentration or load and any of the questions addressing mold or housing disrepair (Table I), or when analyzing using a previously described housing disrepair scale as an independent variable in linear regression (β=0.02, p=0.75 for concentration endotoxin; β=0.014, p=0.82 for load) (23 …”
Section: Associations Between Cleaning Habits Built Environment and mentioning
confidence: 60%
“…These results are consistent with prior literature. 25,58 The household-reported presence of rodents and building size were positively statistically significantly associated with MUP allergen in bivariate and fully adjusted linear models. The household-reported presence of rodents, living in public housing, and building size were statistically significantly associated with MUP allergen at a clinically relevant level of 91.6 μg/g.…”
Section: Discussionmentioning
confidence: 95%
“…23 High levels of indoor allergens are associated with asthma morbidity. 11,[24][25][26] Asthma and sensitization to cockroach allergen are widely known to be associated. [27][28][29] High exposure to cockroach allergen is a risk factor for both asthma medication use and asthma-related hospitalizations.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…In New York City, Rauh et al showed that levels of cockroach allergens and cockroach sightings were associated with degree of housing disrepair and deterioration. 36 In a similar study carried out in Boston, Peters et al found that homes with clutter, lack of cleanliness, and holes in the wall or ceiling had elevated levels of cockroach allergen compared to other urban homes. 37 Serious housing code violations have also been linked to increased cockroach and mice allergen levels in the home.…”
Section: Discussionmentioning
confidence: 96%